KONTEKSTUALSASI DALAM UPAYA PENETAPAN HUKUM ISLAM - Asror, M Khozinul (Program Studi Hukum Ekonomi Syariah, 2023)
In determining or exploring Islamic law, contextual methods can be studied through interpretation or in accordance with developments in science. Understanding Islamic law cannot be done only through the two approaches used by Schacht, namely the historical approach and social science, including legal sociology. However, a comprehensive approach is needed, including all approaches such as theology, philosophy, history and social sciences. Apart from that, a special approach is also needed towards maqāṣid syarī'ah.